2014
DOI: 10.12973/eurasia.2014.1018a
|View full text |Cite
|
Sign up to set email alerts
|

Secondary School Students’ Misconceptions about Photosynthesis and Plant Respiration: Preliminary Results

Abstract: The study investigated the common misconceptions of lower secondary school students regarding the concepts of photosynthesis and plant respiration. These are abstract concepts which are difficult to comprehend for adults let alone for lower secondary school students. Research of the students misconceptions are conducted worldwide. The researches show that many students do not even understand the fundamental concept that photosynthesis and plant respiration are related, mutually connected physiological function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(61 citation statements)
references
References 14 publications
2
43
0
5
Order By: Relevance
“…In Slovenia, most future farmers finish some level of agricultural education, which includes biology either as a separate subject or as biology topics that are part of other agronomical subjects. Previous research indicated that students of different ages find photosynthesis difficult to understand and have inadequate knowledge of it (Domingos-Grillo, Reis-Grilo, Ruiz, & Mellado, 2012, Marmaroti & Galanopoulou, 2006Özay & Öztaş, 2003;Svandova, 2014).…”
Section: Problem Of Researchmentioning
confidence: 99%
“…In Slovenia, most future farmers finish some level of agricultural education, which includes biology either as a separate subject or as biology topics that are part of other agronomical subjects. Previous research indicated that students of different ages find photosynthesis difficult to understand and have inadequate knowledge of it (Domingos-Grillo, Reis-Grilo, Ruiz, & Mellado, 2012, Marmaroti & Galanopoulou, 2006Özay & Öztaş, 2003;Svandova, 2014).…”
Section: Problem Of Researchmentioning
confidence: 99%
“…This perception was supported by research findings which stated that a number of misconception occurred in natural science subject (Akbas & Gencturk, 2011;Thompson & Logue, 2006). One of the misconceptions took place in the topics of photosynthetic and organ systems of the human body (Laksana, Degeng, & Dasna, 2017;Svandova, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Another common misconception is that photosynthesis takes place during the day whereas respiration takes place only at night and in plants (Deshmukh & Deshmukh, 2009). Another research was conducted by K. Svandova in 2014.This research shows that many students do not even understand the fundamental concept that photosynthesis and plant respiration are related, mutually connected physiological functions (Svandova, 2014) Table 1. Percentage of missconception in photosynthesis concepts (Ariandini & Anggraeni, 2013) No…”
Section: Resultsmentioning
confidence: 99%
“…Misconceptions are erroneous perceptins of what is universally accepted. Another term of misconceptions are understood as a misunderstanding of scientific concept (Svandova, 2014).…”
Section: Studiesmentioning
confidence: 99%